Prevalence and Correlates of Frequent and Infrequent Bullying Victimization Among School Adolescents from Five Southeast Asian Countries - Peltzer, Karl; Pengpid, Supa (UI Scholars Hub, 2021)
Background: Little is known about the frequency of bullying victimization (BV) among adolescents in Association of Southeast Asian Nations (ASEAN) member states. This study aims to assess the prevalence and correlates of frequent and infrequent BV among school-going adolescents in five ASEAN member states. Methods: The cross-sectional sample of the Global School-based Student Health Survey (GSHS) of 2015 comprised 33,184 school adolescents (14.6 years mean age) from five ASEAN countries. Students completed a paper-based, self-administered questionnaire on BV in their own languages during classroom periods. Multinomial logistic regression was used to predict frequent and infrequent BV, with no BV as the reference category. Results: Results indicate that 30.6% of participants reported any past-month BV, 33.9% in boys and 27.5 in girls, ranging from 11.8% in Laos to 48.7% in the Philippines. In the adjusted multinomial logistic regression analysis of students from the Philippines and Thailand, experience of hunger, sedentary behavior, attendance at physical education classes, being underweight, overweight, or obese, ever amphetamine use, physical assault, school truancy, participation in a physical fight, injury, low peer support, and psychological distress were all associated with BV. Conclusions: Approximately one in three adolescents was bullied. Several associated variables were identified which can assist in targeting strategies of intervention.